Malaysia's accession to the Rome Statute of the ICC: challenges and the way ahead - Hamid, Abdul Ghafur@Khin Maung Sein (2015)
There are three excuses made by the Malaysian government for its reluctance to accede to the Rome Statute of the ICC: the concern about compatibility with Syari’ah, the position of the Yang di-Pertuan Agong and Malay Rulers; and the Government’s wish to ensure that implementing legislation is in place first before it’s accession to the Rome Statute. The speaker first of all argues that there have been In-depth research and scholarly writings showing that there is generally no conflict between the Rome statute and Shari’ah. In relation to the issue of the immunity of the King and Rules, it is the submission of the speaker that the immunity has been taken away by the Federal Constitution by means of the 1993 amendments and that both under international law and Islamic law official capacity is no bar to prosecution for international crimes. Although implementing legislation is not necessary to be in place first before accession to the Rome statute, it is submitted that Malaysia can use the Common Wealth Model to Implement the Rome Statute.